Vitamins D, C and COVID-19 - А. I. Rusnak (Лечащий Врач)
In the absence of effective treatment for COVID- 19, various drugs were empirically used. Contradictory literature data, from adherents to complete denial of the use of vitamins D and C in COVID-19, prompted us to analyze the literature data and express our opinion on this issue. In our country and abroad, many medical centers include vitamins D and C in the therapy of a new coronavirus infection. Almost all organs and systems of our body have receptors for vitamin D. This fact indicates the active participation of vitamin D in protecting against infection, allergies, and prolonging human life. People with vitamin D deficiency are more likely to have respiratory infections, anemia, muscle hypotension, and bone fragility. The use of vitamin D in coronavirus infection is effective with daily intake of physiological doses of vitamin D. Compensation for vitamin D deficiency is important for the activation of interferon-dependent antiviral immunity, and for the prevention of «cytokine storm», normalization of the coagulation system, and for the reduction of chronic inflammation in the presence of concomitant chronic pathologies in the patient. Even the transition from a severe deficiency of vitamin D (25(OH)D < 20 ng/ml) to a moderate deficiency of 25(OH)D (a metabolite of vitamin D, which is used to judge its supply of the body) in the range of 20-30 ng/ml, in Reduces the risk of admission of a patient with pneumonia to the intensive care unit by 3 times and the risk of transfer to mechanical ventilation by 11 times. The use of vitamin C in coronavirus infection is effective by compensating for its existing deficiency and by interacting with other vitamins. An effective way to maintain the level of vitamins D and C in the population is to fortify these vitamins and other nutrients in foods of mass consumption, as well as to take vitamins in other forms. Multivitamins produced in Western countries are mainly designed for people living in these territories, taking into account the common method of fortifying food. For our country, the norms of consumption of vitamins have been substantiated, confirmed by massive studies of the population of different regions.